2023
DOI: 10.3390/ijms241814348
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Panel Sequencing Identifies a Novel Germline Mutation Profile in Male Breast Cancer Patients

Ayman Al Saati,
Pierre Vande Perre,
Julien Plenecassagnes
et al.

Abstract: Even though male breast cancer (MBC) risk encompasses both genetic and environmental aetiologies, the primary risk factor is a germline pathogenic variant (PV) or likely pathogenic variant (LPV) in BRCA2, BRCA1 and/or PALB2 genes. To identify new potential MBC-specific predisposition genes, we sequenced a panel of 585 carcinogenesis genes in an MBC cohort without BRCA1/BRCA2/PALB2 PV/LPV. We identified 14 genes carrying rare PVs/LPVs in the MBC population versus noncancer non-Finnish European men, predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Based on the observation that PALB2 PV carriers were fourfold more likely to have a male relative with BC than non-carriers [86], several studies have investigated the presence of PALB2 PVs in MBC cases by candidate single-gene sequencing, and more recently by gene-panel sequencing approaches [25,[27][28][29]31,32,85,[87][88][89][90][91][92][93][94][95][96]. These studies showed a variable PALB2 PV frequency, ranging from about 0.8% to 1.8%, depending on the characteristics and the size of the population analyzed [25,27,29,31,32,93].…”
Section: Palb2mentioning
confidence: 99%
“…Based on the observation that PALB2 PV carriers were fourfold more likely to have a male relative with BC than non-carriers [86], several studies have investigated the presence of PALB2 PVs in MBC cases by candidate single-gene sequencing, and more recently by gene-panel sequencing approaches [25,[27][28][29]31,32,85,[87][88][89][90][91][92][93][94][95][96]. These studies showed a variable PALB2 PV frequency, ranging from about 0.8% to 1.8%, depending on the characteristics and the size of the population analyzed [25,27,29,31,32,93].…”
Section: Palb2mentioning
confidence: 99%